Insect Enzymes For Biotechnology Industry: From Nature To Industrial Applications (Journal of Engineering and Health Sciences, 2019)
The demand for enzyme as biocatalyst is increasing for biotechnological based industry. This is due to their ability to catalyze specific biochemical reactions and able to generate products that have significant commercial value. Some of these enzymatic reactions cannot be replicated using conventional organic synthesis process. On the other hand, insects have evolved and established various enzymatic pathways that are not only important for their survival but also valuable. Therefore, scientists and engineers are searching a way to utilize insect’s enzyme for industrial processing as an alternative for greener technology. A high-level idea about how the biological systems work, evolve and interconnect in nature is essential in order to put the application into the industry. A new field of innovation to increase performance and reliability, discoveries are in turn solving some of technology’s greatest challenges as the demand for cleaner and greener technology is rising. This paper will review on the application of insect’s enzyme as a biocatalyst in the field of biopharmaceutical, agricultural, food and pulp and paper industry.